Canadian annual review of politics and public affairs, 1985 - Byers, R. B. ([Toronto, Ont.] : University of Toronto Press, 1988)
The Canadian Annual Review has become an indispensable reference book for those concerned directly or indirectly with Canadian public affairs.Compiled by a corps of Canadian scholars and experts, It offers both a concise, convenient record of the year's events and a responsible appraisal of important developments.Among the events of 1985 analysed in this volume are the activation of the free trade talks with the United States, adding a note of tension to the relationship that in March was serenaded at the Shamrock Summit. In Ontario the forty-year Tory dynasty was ended by an agreement between David Peterson's Liberals and the New Democratic Party. Across the country, relations between the federal and provincial governments improved considerably, in the aftermath of the Mulroney victory in the previous year.
BRITISH COLUMBIA ; PRINCE EDWARD ISLAND ; SASKATCHEWAN ; ALBERTA ; NEWFOUNDLAND AND LABRADOR ; THE YUKON ; THE NORTHWEST TERRITORIES ; Obituaries 1985.
Includes some text in French.
Print version record.
eBooks on EBSCOhost
Keywords: Canada -- Economic conditions -- 1945-; Canada -- Foreign relations -- 1945-; Canada -- Politics and government -- 1945-; Canada -- Politique et gouvernement -- 1935-; Canada -- Relations extérieures -- 1945-; Canada -- Conditions économiques -- 1945-; POLITICAL SCIENCE -- General; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Economic history; Diplomatic relations; Politics and government; Canada; Since 1945